Gift giving characteristics of recipients and function of gifting anxieties - Nomura, Miki. (My University, 2009)
Previous research suggests that gift giving is a form of identity presentation that enables givers to create a desired image of themselves for gift recipients. Sometimes, however, individuals experience anxiety when selecting gifts that best reflect this desired identity (Sherry et al., 1993). Furthermore, the influential power of the gift receiver can create mental stress for the giver. This stress may be reflected in greater physiological arousal and longer decision making time. The purpose of this study was to demonstrate physiologically the anxiety caused by gift giving to influential gift recipients. The results showed that the difficult recipient group registered the highest gifting anxiety as measured by electrodermal response. However, the amount of time spent making gift purchasing decisions was not influenced by either types of recipients or emotional importance. Within the category of difficult recipients, inlaws created the most stress on givers, whereas children and samegender friends produced the least stress.
Keywords: Gifts--Psychological aspects; Gifts; Social psychology